Escala urbana (2004)
Presentación de una propuesta de crecimiento para la ciudad de Vic y de gestión urbanística para El Papiol.
Keywords: PÉREZ I GONZÁLEZ, BLAI; ROLDÁN + BERENGUÉ; ROLDÁN ANDRADE, MIGUEL; BERENGUÉ IGLESIAS, MERCÈ; ESPAÑA; CATALUNYA; BARCELONA; URBANISMO; PLANIFICACION URBANA